Judicial Specialisation in a Generalist Jurisdiction: Is Commercial Specialisation Within the High Court Justified? - Steel, William (Victoria University of Wellington Law Review, 2015)
In November 2013, after a series of Law Commission reports and years of academic, professional and judicial discussion, the Government introduced legislation to Parliament to replace the existing High Court commercial list with a specialist commercial panel. Whilst this panel would bring New Zealand into line with many comparable common law jurisdictions, this article argues that the case for specialisation has not been established. In particular, it notes that there is no publically available evidence to support the claim that the High Court is losing its commercial jurisdiction, or that commercial parties are choosing to resolve their disputes offshore or through alternative dispute resolution. Accordingly, this article argues that future research by the Law Commission, or other research agency, is required before specialisation can be justified. In reaching this conclusion, it also examines the issues that may arise if the Government decides to continue with its proposed reform under cl 18 of the Judicature Modernisation Bill 2013, suggesting changes along the way.